Penerapan Metode Economic Order Quantity dan Reorder Point Pada Aplikasi Pengelolaan Persediaan Fumigasi - Farel Faleri; Pantjawati Sudarmaningtyas; Valentinus Roby Hananto (Journal of Applied Computer Science and Technology, 2023)
Fumigation controls pests by sealing a room using methyl bromide (CH3Br) and oxygen gas. This process requires a gas mask, fumigation plastics, sand snakes, and a certificate. The interview revealed that specific supply shortages cause fumigation delays in 15% of monthly orders. This research aims to develop an inventory control application by applying the economic order quantity (EOQ) and reorder point (ROP) methods to overcome the problem of running out of stock. The EOQ method determines the amount of inventory to order to avoid excess stock, while ROP determines the right time to order inventory. The study involved two types of testing: white box testing and comparing manual calculations with application calculations to determine their consistency using data from March to May. The white box testing results show that the program's internal structure and logic run well. This is supported by evidence that each test case can pass two flow graphs resulting from cyclomatic complexity calculations. In addition, the results of testing the EOQ and ROP method calculations show an insignificant difference between the results of manual calculations and application calculations of 3.87%. This proves that application calculations for EOQ and ROP are running correctly and by the researchers' expectations.